Is Conveying Knowledge the Only Task of the Contemporary School? - Marian Nowak (Nicolaus Copernicus University in Toruń, 2012)
While analyzing the objectives of the contemporary school, the article concentrates on its two main goals: conveying knowledge as well as providing moral, social and cultural development. Reaching to the past − the period of Reformation and the idea of predestination, still present today in some Protestant factions − the author demonstrates how this idea affects not only the concept of man in Europe, but also the idea of education and the acceptance or rejection of the so-called "educational capability", on which J.F. Herbart, amongst others, based the possibility of building pedagogy as an autonomous discipline. The idea of predestination was accepted by J.A. Komeński (Comenius) and others, and it was characterized by giving importance and even possibility of merely conveying knowledge and resulted in restricting the role of school and lessons only to teaching. The acceptance of the category of educability and relative lack of determination in human education − free from the idea of predestination − evident, for instance, in the teaching and educational tradition of the Catholic Church and the Eastern Churches, resulted in not only the position of pedagogical realism, but also in the assignment of both educational and didactic objectives to school. The article points to the continuous influence of this theoretical and ideological foundation on undertaken decisions and existing models of the present day school education. Based on anthropological and historic foundations of educational and didactic concepts in reference to main objectives of school, the article points to possible solutions for linking education and instruction, establishes consequences for contemporary models of school functioning, with the focus on teaching (didactic function), or on teaching and moral instruction (educational and didactic function), and then presents conceptual models of lessons and school functioning while taking into consideration both teaching and instruction: 1) the instructive lesson (J.F. Herbart); 2) the educational lesson (W. Klafki) and 3) the school life (C.G. Scheibert). The indicated models can be helpful in implementing the recommendations of the Core Curriculum of Polish schools (both the previous and the new Core Curriculum), that draw attention to both teaching and instruction of students in Polish schools. As Pope Benedict XVI demonstrated in his Letter to the Roman diocese in 2008, both objectives can be the answer to "an urgent need of education", overcoming the wrong tendency of transferring to students only the skills or abilities to act, and quenching the young generations' thirst for happiness with things of consumer nature. Thus representing the view of the Catholic Church, once again and in accordance with the position of defending a human being as a person which is known from history, the Pope opposes the diminishing and restricting of the objectives of school and appeals for a more evident implementation of not only didactic but also educational function of the modern school.